2002
DOI: 10.1210/en.2002-220413
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A-Dependent Cooperation between GATA and CCAAT/Enhancer-Binding Protein Transcription Factors Regulates Steroidogenic Acute Regulatory Protein Promoter Activity

Abstract: Steroidogenic acute regulatory protein (StAR) is an essential cholesterol transporter in steroidogenic tissues. Hormone-induced StAR expression is regulated through the cAMP-dependent pathway involving activation of protein kinase A (PKA). The StAR promoter contains several conserved DNA regulatory elements. These include binding sites for steroidogenic factor 1, CCAAT/enhancer-binding protein (C/EBP), and GATA transcription factors. Although these elements are important for StAR promoter activity, how the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 61 publications
4
103
2
Order By: Relevance
“…Consistent with this, there have been numerous reports of direct protein-protein interactions involving these transcription factors on the Star promoter in Leydig cells (Reinhart et al 1999, Sugawara et al 2000, Tremblay et al 2002, Manna et al 2003b. In the present study, we have found that NUR77 and c-JUN have additive effects on the mouse Star promoter in Leydig cells.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Consistent with this, there have been numerous reports of direct protein-protein interactions involving these transcription factors on the Star promoter in Leydig cells (Reinhart et al 1999, Sugawara et al 2000, Tremblay et al 2002, Manna et al 2003b. In the present study, we have found that NUR77 and c-JUN have additive effects on the mouse Star promoter in Leydig cells.…”
Section: Discussionmentioning
confidence: 76%
“…All proteins were obtained using the Quick Coupled TnT in vitro transcription/translation kit (Promega Corp, Madison, WI, USA). Proteins were incubated in 500 ml binding buffer (Tremblay et al 2002) with 4 mg NUR77, c-FOS, or c-JUN antisera for 24 h at 4 8C with agitation, followed by an additional 24 h in the presence of 20 ml protein G-Sepharose beads (GE Healthcare, Baie d'Urfe, QC, Canada). Bound immunocomplexes were washed five times in binding buffer, resuspended in 20 ml 2!…”
Section: Protein-protein Interaction Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The promoter activity of GATA-6, in turn, is activated by PKA by phosphorylation on a unique serine (25).…”
Section: Resultsmentioning
confidence: 99%
“…In normal tissue, PKA is involved in many cellular functions (23). It phosphorylates many targets, including transcription factors such as cAMP response element-binding protein (CREB) (24), GATA3, GATA6 (25), NF-κB (26), β-catenin [activating downstream elements of the wnt pathway (27)], the transcription coactivator yes-associated protein 1 (YAP) (28), and ETV1 (29) and indirectly activates XBP1 (30). Any or all of these molecular events could have significant effects on gene expression.…”
mentioning
confidence: 99%